Ovarian tissue transplantation: 10 years of experience at the Bologna University - Fabbri, Raffaella; Vicenti, Rossella; Magnani, Valentina; Paradisi, Roberto; De Meis, Lucia; Raimondo, Diego; Arena, Alessandro; Venturoli, Stefano; Raffone, Antonio; Raspollini, Arianna; Seracchioli, Renato (Frontiers in Endocrinology, 2024)
Objective: The efficiency of ovarian tissue transplantation (OTT) was established in terms of ovarian function recovery (95% of cases), number of live births (over 200 wordwide to date) and induction of puberty. Unfortunately, the lack of international registries and the fact that many centers have not yet reported their outcomes, lead to poor knowledge of the exact fertility data. The aim of the study is to describe our experience with OTT to restore ovarian function and fertility.Methods: This study was designed as a single-center, observational, retrospective, cohort study that includes women who underwent OTT between December 2012 and June 2023 at our center. After approval by the oncologist/hematologist, a small fragment of ovarian tissue was thawed and analysed to detect the presence of micrometastases before OTT. Thawed ovarian tissue was grafted laparoscopically at multiple sites, including the remaining ovary and pelvic side wall (orthotopic transplantation) and/or abdominal wall (heterotopic transplantation). After OTT, ovarian function was monitored by hormonal assay, ultrasound and color Doppler at approximately 4-week intervals.Results: Between December 2012 and June 2023, 30 women performed OTT. Prior to OTT, immunohistochemical and molecular analyses revealed no micrometastases in all thawed ovarian tissue samples. In our series of 30 women, 20 of women were on premature ovarian insufficiency (POI), and the remaining ten cases still had oligomenorrheic menstruation and difficulty getting pregnant. Among the women with POI before OTT and at least 6 months follow-up, recovery of endocrine function was observed in all but one woman who underwent orthotopic transplantation (11 of 12 cases), in one out of two women who underwent both orthotopic and heterotopic transplantation (1 of 2 cases) and in all women who underwent heterotopic transplantation (4 of 4 cases). Women who underwent OTT to enhance fertility had no alterations in menstrual cycle and hormonal levels. In total, eight pregnancies were obtained in 21 women, resulting in four live births, one ongoing pregnancy and three spontaneous abortions. 4 Conclusion: Our data can help patients and physicians in their discussions and decisions about the need and possibilities of preserving fertility.